Quadrature Spatial Modulation Decoding Complexity: Study and Reduction - Al-Nahhal, Ibrahim; Dobre, Octavia A.; Ikki, Salama S. (IEEE wireless communications letters, 2017)
This letter presents the computational complexity reduction of the maximum likelihood-quadrature spatial modulation (QSM-ML) decoder as compared with the conventional SM-ML. Furthermore, a novel reduced-complexity (RC) sphere decoder algorithm, especially designed for QSM decoders, is proposed. It is shown that the QSM-RC algorithm achieves the optimum QSM-ML bit error ratio performance. Using Monte Carlo simulations and mathematical analysis, at the same spectral efficiency and with notable superior performance, it is shown that the QSM-ML and QSM-RC decoders provide at least 50% and up to 96% reduction in the number of visited nodes, respectively, compared to the SM-ML decoder.